The Effects of Agility Training on Abilities of Dribbling the Ball - Lertwilai, Monrak (Journal for Developing the Social and Community, 2021)
Abstract This research article aimed to study the agility practicing program of footballers’ dribbling skills; and to compare the differences between agility practicing with specificity training of dribbling and the specific training program of dribbling only the ball. It is an experimental research. The sample in this study were 20 female footballers of Phuket Rajabhat University; who were Studying in the first Year to the fourth year of academic year 2016 and 20 female footballers of British international school, Phuket. The participants were divided into two groups: one was a controlled group which consisted of 20 female footballers; and another was an experimental group which also comprised of 20 female footballers. The purposive sampling. Tools used for data collection Training program with agility. Agility measuring tool and a record sheet of training results before and after training. The findings can be concluded as follows. The comparisons of agility towards dribbling the ball between the controlled group and the experimental group before and after on the week 4 and week 8 of the practicing and it were found that; 1.1) The agility towards dribbling skill of the controlled group and the experimental group before the practicing were not different. 1.2) The agility towards dribbling skill of the experimental group after week 4 of practicing differed from the controlled group significantly at.05. 1.3) The agility towards dribbling skills of the experimental group after week 8 of practicing differ from the controlled group significantly at.05. The agility towards skill of the controlled group before and after the practicing on week 4 and week 8 were significantly different at 0.05. 3. The agility towards dribbling skills of the experimental group before practicing and after practicing on week 4 and 8 were found significantly different at.05